KNOWLEDGE AND PRACTICES OF SAFE USE OF PESTICIDES AND ASSOCIATED FACTORS AMONG THE HIRED SPRAYERS IN THANH BINH DISTRICT, DONG THAP PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the knowledge and practice of safe use of pesticides and identify associated factors among the hired sprayers in Thanh Binh district, Dong Thap province in 2021.Methods: A cross-sectional study was conducted in four communes of Thanh Binh district with a sample size of 200 hired sprayers. Descriptive and analytic biostatistics techniques were applied at significance level of 0.05.Results: The percentage of researchers with correct knowledge and appropriate practices was above the average level, i.e. 64.5% and 63%, respectively. The researchers who participated in the training had higher correct practice than those who did not participate in the training (p < 0.05%).Conclusion: The appropriate practices of safe use of pesticides average. Participation in training course on pesticides was associated to the appropriate practices of safe pesticide usage.
Keywords: Hired sprayers, pesticides, knowledge, practices, Thanh Binh, Dong Thap.